Risk of neoplasms in acromegaly - Ruchała, Marek (Termedia Publishing House, 2012)
Acromegaly is a chronic disease caused by the excessive secretion of growth hormone (GH), and as a result, of insulin-like growth factor-1 (IGF-1). Untreated, the condition reduces the patients’ life expectancy and leads to a series of complications, among which an increased risk of carcinogenesis is considered most important. This paper is an analysis of the publications on the issue of the formation of neoplasms, both malignant and benign, in acromegalic patients. Although the influence of acromegaly on carcinogenesis remains controversial, a number of studies indicate that the frequency of developing tumors in this patient group is higher. Moreover, numerous publications particularly stress the increased risk of developing neoplasms in patients who had been untreated for a long period of time and show elevated levels of GH and IGF-1. Consequently, a quick diagnosis and the implementation of effective treatment play a key role in the management of this disease.